Gut microbiome and metabolome in aneurysm rat with hypertension after ginsenoside Rb1 treatment - Zeng, Zhaobin; Wang, Haibin; Yi, Renhui; Lou, Jianyun; Wen, Shuting; Hu, Zheng (Frontiers in Pharmacology, 2023)
Introduction: Hypertension is a well-known risk factor for aneurysms, as high blood pressure can worsen the development and rupture of aneurysms. Ginsenoside, derived from ginseng and widely used in traditional herbal medicine, is believed to have antihypertensive properties. Recent research has also shown a connection between gut microbiota and various diseases, including hypertension. However, the relationship between ginsenosides, gut microbiota, blood pressure, and intracranial aneurysms needs further exploration. Methods: In this study, a rat model was used to investigate the effects of ginsenosides on both blood pressure and intracranial arteries. Comparative analysis was conducted, and 16S rRNA sequencing was employed to identify marker genera within the gut microbiota. Metabolites were also analyzed to uncover potential mediators of blood pressure regulation. Results and Discussion: The results of this study revealed that ginsenosides, particularly ginsenoside Rb1, demonstrated positive effects in reducing both blood pressure and the development of intracranial aneurysms in rats. Furthermore, the analysis of gut microbiota showed that certain genera, including Clostridium, Roseburia, Ruminococcus, and Treponema, were significantly influenced by ginsenoside treatment. Several metabolites, such as behenic acid, N-Acetylserotonin, Prostaglandin F2a, and Vitamin D2, were also detected, all of which play a role in regulating blood pressure. These findings provide valuable insights into the potential benefits of ginsenosides in hypertension and atheroma development. Furthermore, they suggest a possible link between ginsenosides, gut microbiota, and blood pressure regulation. Further research is needed to fully understand the mechanisms underlying these effects and to determine the clinical implications for treating hypertension and reducing the risk of aneurysm development.